A predictive micropolar continuum model for a novel three-dimensional chiral lattice with size effect and tension-twist coupling behavior. (December 2018) - Duan, Shengyu; Wen, Weibin; Fang, Daining
Highlights: A novel three-dimensional cubic chiral lattice is proposed by introducing noncentrosymmetry into microstructure design. Independent micropolar elastic constants of the proposed 3D chiral lattice are deduced and a homogenization method is developed. The proposed constitutive model is able to predict the size effect and tension-twist coupling behavior of the proposed 3D chiral lattice. This work establishes a fundamental link between the macroscopic mechanical properties and microstructure of 3D chiral material. Abstract: This work extends the micropolar theory for the constitutive behaviors of three-dimensional (3D) cubic chiral lattice. A novel 3D chiral lattice is proposed by introducing noncentrosymmetry into microstructure design of artificial materials. The independent micropolar elastic constants of the proposed 3D chiral lattice are deduced and divided into the isotropic and anisotropic types with orthogonal irreducible decomposition of tensor. A homogenization method for the proposed 3D chiral lattice is developed to solve mathematical relations between the elastic constants and structure parameters of the chiral lattice which are admitted by finite element (FE) analysis. Two representative numerical examples are analyzed with the FE model and the continuum model where the size effect and tension-twist coupling behavior of the proposed 3D cubic chiral lattice are accurately predicted. This work establishes a fundamental link between the macroscopic mechanical properties and microstructure of the chiral material, and provides a new channel for 3D chiral microstructure design. Graphical abstract: Image, graphical abstract